Join the conversation on IDNLearn.com and get the answers you seek from experts. Ask any question and receive timely, accurate responses from our dedicated community of experts.
Sagot :
Answer:
[tex]\displaystyle a = 0 \text{ and } b = 1[/tex]
Step-by-step explanation:
We are given that:
[tex]\displaystyle \frac{7 + 3\sqrt{5}}{3 + \sqrt{5}} - \frac{7 - 3\sqrt{5}}{ 3 - \sqrt{5}} = a + \sqrt{5b}[/tex]
And we want to determine the values of a and b.
Simplify the fractions. We can multiply each by the conjugate of its denominator:
[tex]\displaystyle \frac{7 + 3\sqrt{5}}{3 + \sqrt{5}} \left(\frac{3-\sqrt{5}}{3-\sqrt{5}}\right) - \frac{7 - 3\sqrt{5}}{3 - \sqrt{5}} \left( \frac{ 3 + \sqrt{5}}{3 + \sqrt{5}}\right)[/tex]
Simplify:
[tex]\displaystyle = \frac{(7 + 3\sqrt{5})(3 - \sqrt{5})}{(3)^2 - (\sqrt{5})^2} - \frac{(7 - 3\sqrt{5})(3 + \sqrt{5})}{(3)^2 - (\sqrt{5})^2} \\ \\ \\ = \frac{(21 - 7\sqrt{5} + 9\sqrt{5} - 3(5))}{(9) - (5)} - \frac{(21+ 7\sqrt{5} - 9\sqrt{5} -3(5))}{(9) - (5)} \\ \\ \\ = \frac{21 + 2\sqrt{5} - 15}{4} - \frac{21 -2\sqrt{5}-15}{4} \\ \\ \\ = \frac{(6 + 2\sqrt{5})-(6-2\sqrt{5})}{4} \\ \\ \\ = \frac{4\sqrt{5}}{4} \\ \\ = \sqrt{5} = 0 + \sqrt{5(1)}[/tex]
In conclusion, a = 0 and b = 1.
[tex]\large \sf \underline{Solution - }[/tex]
[tex] \rm Given \: : \: \dfrac{7 + 3 \sqrt{5} }{3 + \sqrt{5} } - \dfrac{7 - 3 \sqrt{5} }{3 - \sqrt{5} }= a + \sqrt{5b} [/tex]
- Here, we have to find the value of a and b.
➢ Multiplying the conjugate of their denominator to both the fractions.
So,
[tex] \rm \: \implies \dfrac{7 + 3 \sqrt{5} }{3 + \sqrt{5} } - \dfrac{7 - 3 \sqrt{5} }{3 - \sqrt{5} }= a + \sqrt{5b} [/tex]
[tex] \rm \: \implies \dfrac{(7 + 3 \sqrt{5})(3 - \sqrt{5}) }{(3 + \sqrt{5} )(3 - \sqrt{5})} - \dfrac{(7 - 3 \sqrt{5}) (3 + \sqrt{5})}{(3 - \sqrt{5})(3 + \sqrt{5}) }= a + \sqrt{5b} [/tex]
We know,
[tex] \rm\implies (a - b)(a + b) = (a)^{2} - (b)^{2}[/tex]
Then,
[tex] \rm \: \implies \dfrac{(7 + 3 \sqrt{5})(3 - \sqrt{5}) }{3^{2} - ( \sqrt{5} )^{2} } - \dfrac{(7 - 3 \sqrt{5}) (3 + \sqrt{5})}{3^{2} - ( \sqrt{5} )^{2} } = a + \sqrt{5b} [/tex]
[tex] \rm \: \implies \dfrac{(7 + 3 \sqrt{5})(3 - \sqrt{5}) }{9- 5 } - \dfrac{(7 - 3 \sqrt{5}) (3 + \sqrt{5})}{9 - 5 } = a + \sqrt{5b} [/tex]
[tex] \rm \: \implies \dfrac{(7 + 3 \sqrt{5})(3 - \sqrt{5}) }{4} - \dfrac{(7 - 3 \sqrt{5}) (3 + \sqrt{5})}{4 } = a + \sqrt{5b} [/tex]
Combine both the fractions,
[tex] \rm \: \implies \dfrac{(7 + 3 \sqrt{5})(3 - \sqrt{5}) - (7 - 3 \sqrt{5}) (3 + \sqrt{5})}{4} = a + \sqrt{5b} [/tex]
[tex] \rm \: \implies \dfrac{21-7\sqrt{5}+9\sqrt{5}-15-21-7\sqrt{5}+9\sqrt{5}+15}{4}= a + \sqrt{5b} [/tex]
[tex] \rm \: \implies \dfrac{4 \sqrt{5} }{4}= a + \sqrt{5b} [/tex]
[tex] \rm \: \implies \sqrt{5} = a + \sqrt{5b} [/tex]
[tex] \rm \: : \implies 0 + \sqrt{5 \times 1} = a + \sqrt{5b} [/tex]
Therefore, we notice that
- The value of a is 0
- The value of b is 1
Thank you for joining our conversation. Don't hesitate to return anytime to find answers to your questions. Let's continue sharing knowledge and experiences! IDNLearn.com has the solutions you’re looking for. Thanks for visiting, and see you next time for more reliable information.